Is Agricultural Institutions Affect the Sustainability of Local Adan Rice Farming? - Khaerunnisa; Etty Wahyuni MS; Didi Rukmana; Saat Egra; Masitah; Fitriani R; Ayu Wulandari (Universitas Hasanuddin, 2023)
Krayan's main commodity is Adan rice which has received a Geographical Indication Certification (GIS). This rice has high economic value and competitiveness because it is cultivated organically. Therefore, local rice commodities need to be cultivated in a sustainable manner. One dimension of local rice sustainability is the institutional dimension. The institutional dimension is an important for sustainable agricultural development because it plays a supporting role in the success of farming. This study aims to analyze the sustainability of local Adan rice farming on the institutional dimension in Krayan District, Nunukan Regency, Indonesia. This research was completed by using the Multi Dimensional Scaling Method and sample was obtained of 50 respondents. The results showed that the institutional dimension of local Adan rice farming in Krayan District was 58.41 which means the institutional dimension has an affect on the sustainability of Adan rice farming in Krayan sub-district with a quite sustainable status. The results of the analysis of sensitive attributes on the institutional dimension are capital loans from financial institutions (banks or other capital assistance institutions), the existence of cooperative institutions, capital assistance from cooperatives and Membership in indigenous forums. This implies that, considering all sensitive attributes of institutional dimension are important aspect to support the sustainability of local Adan rice farming.